2014
DOI: 10.1002/2014gl061820
|View full text |Cite
|
Sign up to set email alerts
|

Observation of collisionless shocks in a large current‐free laboratory plasma

Abstract: We report the first measurements of the formation and structure of a magnetized collisionless shock by a laser-driven magnetic piston in a current-free laboratory plasma. This new class of experiments combines a high-energy laser system and a large magnetized plasma to transfer energy from a laser plasma plume to the ambient ions through collisionless coupling, until a self-sustained M A ∼ 2 magnetosonic shock separates from the piston. The ambient plasma is highly magnetized, current free, and large enough (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
61
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 25 publications
2
61
0
Order By: Relevance
“…In this proceeding, we present measurements of the resonant right-hand instability in our experiment and compare them with predictions of shock-formation theory [17]. This research continues previous work on the generation and investigation of a perpendicular collisionless shock [18,19]. …”
supporting
confidence: 72%
“…In this proceeding, we present measurements of the resonant right-hand instability in our experiment and compare them with predictions of shock-formation theory [17]. This research continues previous work on the generation and investigation of a perpendicular collisionless shock [18,19]. …”
supporting
confidence: 72%
“…However, this process has never before been observed in a laboratory setting. Despite numerous experiments utilizing laser-produced plasmas to simulate space and astrophysical explosions 22 , including noteworthy recent studies that successfully generated magnetized collisionless shocks 23,24 and measured the electrostatic component of the electric field structure associated with an explosive plasma cloud 25,26 , none of these efforts examined the ion dynamics in sufficient detail to confirm Larmor coupling as a participating momentum exchange mechanism.…”
mentioning
confidence: 99%
“…Successful generation of collisionless MHD [45,46] and ES shocks, and experimental approach to study collisionless EM shock [60][61][62]64,65] in laboratory indicate that laboratory experiment can be an alternative approach to study space and astrophysical plasma physics. Furthermore, recent achievement of mono-energetic proton acceleration by collisionless ES shock produced by ultrahigh-intensity laser system [84][85][86] shows a possibility to apply the collisionless shock to several applications including medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recentry, Niemann et al have reported the first observation [45,46] of collisionless MHD perpendicular shock, which was predicted by hybrid-simulation [47], using the Large Plasma Device [48] and a high-energy laser system [49]. No clear particle acceleration has been investigated experimentally for the MHD shock yet.…”
Section: Introductionmentioning
confidence: 99%